ANALISIS TERHADAP PEMAHAMAN AKUNTANSI PENYUSUN LAPORAN KEUANGAN BKM - Djuharni, Darti (JURNAL MANAJEMEN DAN AKUNTANSI, 2012)
Abstract: Research entitled “Survey on BKM Financial Statement Preparers’ Accounting Understanding at Kabupaten Malang and Kabupaten Kota Baru – South Kalimantan” is performed to determine the extent of the preparers understanding on the financial statement. The result of the research is expected to provide benefits to various interested parties, especially to the government, BKM manager and for further researchers. Based on the results of the research can be concluded that most of BKM financial statement preparer at Kabupaten Malang has adequate knowledge on accounting. This is indicated also by the level of education, experience and their readiness to understand their work. While in Kabupaten Kota Baru some of financial statement preparer still has little understanding on accounting especially about financial statement. This is indicated also by the level of education, experience and their readiness to understand their work.  In connection with the above condition, it is expected that government will give more serious attention by giving proportional reward to the preparer based on their job and responsibility. While the BKM manager is also expected to give attention, especially in intensive assistance in order to give the preparers more understanding about what they should do. The assistance for the preparers of financial statement can be done by making cooperation with universities, because lecturers can give community service through this activity as a part of “Tridharma Perguruan Tinggi”. Keyword: Accounting Understanding